R2 and R2* MRI assessment of liver iron content in an undifferentiated diagnostic population with hyperferritinaemia, and impact on clinical decision making. Issue 135 (February 2021) - Craft, Melissa L.; Edwards, Morgan; Jain, Tarun Pankaj; Choi, Philip Y.
Highlights: R2* is accurate in hyperferritinaemia, and highly correlated with R2 (Ferriscan®). R2 and R2* MRI results altered clinical management in >44 % of patients with hyperferritinaemia. R2* has advantages over R2, particularly simultaneous production of a PDFF map. Abstract: Purpose: To confirm the linear correlation between Ferriscan® R2 (1/T2 Relaxomatry) and R2* (1/T2* Relaxometry) derived 3D Gradient echo (GRE) mDIXON-Quant sequence (Philips) with simultaneous production of a proton density fat fraction (PDFF) in undifferentiated patients with hyperferritinaemia, and to prospectively determine the clinical utility of this tool in these patients by recording the impact on clinical decision-making. Materials and Methods: Participants referred to a hospital haematology outpatient clinic for investigation and management of elevated serum ferritin (two serum ferritin levels > 500 μg/L 4 weeks apart) were included in the study. Exclusion criteria: contraindications to MRI; clinically relevant investigations for alternative causes of hyperferritinaemia pending; and terminal illness. Thirty-two participants were recruited: 27 men, 5 women. All MRIs performed at 1.5 T. For R2* quantification, 3D six echo GRE sequence (mDIXON-Quant) was acquired. R2 images were acquired over 20 min as dictated and reported by the licensee (Ferriscan®). Clinician interpretation and patient management based on R2* and liver iron content derived from R2 (LICR2 ) was recorded. Pearson's correlations, linear regression analyses, and ROC curves were calculated. P value <0.05 was considered significant. Results: A high degree of correlation between mean R2* and LICR2 was observed in this novel patient population (slope ± SE of 43.35 ± 1.88 s −1 permg/g; 95 % CI 39.5–47.2; P < 0.001; R 2 = 0.87). Clinical decision making was amended in 14/32 (44 %) patients with hyperferritinaemia following the disclosure of R2* results to clinicians, compared with serum ferritin alone. Liver biopsy was avoided in one patient based on LICR2 and R2*. Unrecognised hepatic steatosis was diagnosed in one patient from the PDFF map. Conclusion: We have confirmed the linear correlation between R2 and R2* in a real-world diagnostic population with hyperferritinaemia. Non-invasive assessment of liver iron content (LIC) by R2 and R2* MRI is a useful clinical tool and alters management in these patients.